Stratigraphic characteristics of quaternary deposits on the left bank of the Sava River near Belgrade - Knežević Slobodan (Geološki Anali Balkanskoga Poluostrva, 2018)
Quaternary deposits on the banks of the Sava River in the Belgrade area have a significant thickness and they are represented by genetically different formations. The data about these sediments were obtained by exploration of two relatively shallow boreholes, RB 47/P-1 and RB 53/P-1, located on the left bank of the Sava River. Two genetic entities are distinguished: the lacustrine-palustrine deposits of Plio-Pleistocene age and alluvial deposits of Pleistocene and Holocene age. Deposits of the Plio-Pleistocene are clearly different, both lithologically and palaeontologically, from the overlying alluvial deposits. Lithologically similar fluvial deposits of the Pleistocene and Holocene age were distinguished according to their palaeontological characteristics, particulary by the presence of bivalve genera Corbicula and Dreissena. [Project of the Serbian Ministry of Education, Science and Technological Development, Grant no. 176015 and Grant no. 177023]